2016
DOI: 10.4236/ce.2016.79134
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Educational Material Using Augmented Reality for Teaching the Module of “Representation of the Information on Computers” in Junior High School

Abstract: The purpose of this study was the investigation of the added value of technology of Augmented Reality in education and, particularly, whether this contributes to both student performance improvement, as well as the appearance of the psychological condition of Flow, which, according to research, has had a positive effect on their performance when experienced during learning process. The research involved a total of 42 students in their second year of junior high school who were taught the module "representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
(111 reference statements)
0
13
0
3
Order By: Relevance
“…Different types of data collection methods also are used to evaluate, typically, a specific evaluation factor by one study, such as Flow Experience (5 studies) Zhang et al, 2014;Giasiranis & Sofos, 2016;Hsu, 2017;Giasiranis & Sofos, 2017). Among the studies that evaluated Flow Experience, two studies reported the use of Flow State Scale (FSS) (Giasiranis & Sofos, 2016;Giasiranis & Sofos, 2017), Teacher Communication Behavior Questionnaire (TCBQ) (Yang & Liao, 2014), Collaborative Inquiry Learning Behavior , Index of Learning Styles (ILS) (Hsu, 2017;Mahmoudi et al, 2017) (2 studies) and VAK Learning Styles Self-Assessment Questionnaire (Zhang et al, 2016), Conceptual Survey of Electricity (CSE) (Echeverría et al, 2012), Bipolar…”
Section: Resultsmentioning
confidence: 99%
“…Different types of data collection methods also are used to evaluate, typically, a specific evaluation factor by one study, such as Flow Experience (5 studies) Zhang et al, 2014;Giasiranis & Sofos, 2016;Hsu, 2017;Giasiranis & Sofos, 2017). Among the studies that evaluated Flow Experience, two studies reported the use of Flow State Scale (FSS) (Giasiranis & Sofos, 2016;Giasiranis & Sofos, 2017), Teacher Communication Behavior Questionnaire (TCBQ) (Yang & Liao, 2014), Collaborative Inquiry Learning Behavior , Index of Learning Styles (ILS) (Hsu, 2017;Mahmoudi et al, 2017) (2 studies) and VAK Learning Styles Self-Assessment Questionnaire (Zhang et al, 2016), Conceptual Survey of Electricity (CSE) (Echeverría et al, 2012), Bipolar…”
Section: Resultsmentioning
confidence: 99%
“…Digital augmentation reshapes experiences for even more people due to the advances in mobile technology and the widespread use of mobile devices in the public and in more and more fields. Mobile technology contributes positively in education [2,3], and augmented reality (AR) along with virtual reality (VR) and mixed reality (MR) are considered to be "key educational technologies over the next decade" [4] (p. 46).…”
Section: Introductionmentioning
confidence: 99%
“…In Greece the use of AR technology in education is limited [3] and thus it is important to study the key factors that can affect its future acceptance and effective use in the educational process. Teachers are the common element in every different educational system and play a key role in the integration and acceptance of technology in education.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Stefanos Giasiranis et al [7] in 2016 investigated whether augmented reality or web-based technology can improve student's performance in the class by teaching a module to a junior high school class. Results obtained from the experiment have shown visible signs of improvement in students with AR technology.…”
Section: Introductionmentioning
confidence: 99%